Infantile Frey's syndrome. Issue 6 (June 2015) - Tillman, Brittny N.; Lesperance, Marci M.; Brinkmeier, Jennifer V.
Abstract: Frey's syndrome in children is rare and often erroneously attributed to food allergy. Here we describe a case of Frey's syndrome in an infant and provide a review of the literature. Awareness of this condition is important for the Otolaryngologist in order to avoid unnecessary medical costs and procedures and provide reassurance to both parents and primary care providers in the setting of this benign condition.